(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Winarni NL, Anugra BG, Anisafitri S, Kaunain NN, Pradana DH. 2021. Fieldwork during pandemic: Backyard bird survey and making student’s biological field practice works. Biodiversitas 22: 1887-1894. The COVID-19 pandemic situations had forced universities to shutdown face-to-face lectures and change it to online teaching. This change had brought significant challenges to biological courses which need field practice in their syllabus and therefore field practice should be adjusted and innovative. During November-December 2020, we compared students’ field practice from the Ornithology class to urban bird survey to evaluate whether the data collected by students can contribute to citizen science as well as to enhance field practice during online courses. We used point count methods to survey bird communities in urban environment in Jakarta and its satellite cities. We found that the students tended to observe the most abundant birds such as the cave swiftlet and Eurasian tree sparrow and missed unfamiliar species which were smaller-sized birds that use aerial and upper canopy. It was suggested that the data from field practice can also support citizen science when prioritized to common, abundance species. In addition, best practices for field practice were provided, emphasizing the independent field practice incorporating technology in which the results were communicated to the students. Hence, strengthening field practice for biological courses is important to support biodiversity conservation research and activities.